The significance of social determinants of health on the outcome of surgical neonates in a third world setting - Brown, Sara; Millar, Alastair J. W.; Cox, Sharon G. (Pediatric surgery international, 2016)
Purpose We aimed to determine whether the outcome of general surgery neonates, cared for within our unit, was influenced by socio-economic status as measured by a selection of social variables [primary caregiver’s education level, primary caregiver’s age, and living standards measure (LSM)] and to determine the rate for each of the three levels of the outcome measure (i.e., good outcome, poor outcome, and deceased). Methods A consecutive sampling strategy was used, including all subjects in our neonatal data base with major surgical diagnoses operated on between 1 July 2010 and 31 August 2011. The primary caregiver of each patient was questioned with respect to the variables and these results were analysed along with clinical information from patient records. Multinomial logistic regression was used to answer both objectives. Results The final multinomial logistic model is highly significant and includes only LSM as a predictor variable. As LSM increases by one level, the risk of experiencing a poor outcome decreases by 82 % as compared to those patients experiencing a good outcome. As LSM increases by one level, the risk of neonatal death also decreases by 88 % as compared to those patients experiencing a good outcome. Conclusion This study shows that the probability of a neonate having a good outcome increases with increasing LSM.